2011
DOI: 10.1007/s15010-011-0121-9
|View full text |Cite
|
Sign up to set email alerts
|

Clinical aspects of 2009 pandemic influenza A (H1N1) virus infection in Austria

Abstract: During the 2009 H1N1 influenza pandemic, elderly or obese patients and those with neurological disease had an increased risk for severe H1N1 infection in Austria. Pregnancy was not associated with a higher risk for severe disease in the later phase of the 2009 H1N1 pandemic. Antiviral treatment provided a minimal effect on the symptoms of influenza but reduced the risk of admission to an ICU.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
55
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(62 citation statements)
references
References 35 publications
6
55
1
Order By: Relevance
“…In the current study, 60.9% of cases had an accompanying risk factor, which is a similar finding in previously mentioned studies. In addition to chronic disease and immunosuppression, the risk of H1N1 influenza infection increases during pregnancy 2,5,[18][19][20][21] . In a study of pregnant women with serious influenza infection conducted in Australia, the relative risks of hospitalisation, admittance to ICU, and death were determined to be 5.2, 6.5, and 1.4, respectively 23 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the current study, 60.9% of cases had an accompanying risk factor, which is a similar finding in previously mentioned studies. In addition to chronic disease and immunosuppression, the risk of H1N1 influenza infection increases during pregnancy 2,5,[18][19][20][21] . In a study of pregnant women with serious influenza infection conducted in Australia, the relative risks of hospitalisation, admittance to ICU, and death were determined to be 5.2, 6.5, and 1.4, respectively 23 .…”
Section: Discussionmentioning
confidence: 99%
“…In 2009, millions of people worldwide were affected by the rapid person-to-person spread of the H1N1 influenza A virus 1,2 . In June 2009, the World Health Organisation (WHO) declared a level 6 warning for this new influenza pandemic th of November 2009 as the first critically ill patient with respiratory failure due to H1N1 infection.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The percentages of missing data were smaller for the deaths than the survivors (0.4% vs. 36% for time to death/discharge for example), suggesting that data collection was more thorough for patients who died. 210 Poeppl 2011 198 Blumental 2011 202 Yung 2011 195 Altmann 2011 185 Enstone 2011 192 del Rosal 2011 205 Nguyen-Van-Tam 2010 186 Thompson 2011 188 Miranda-Choque 2011 197 Yokota 2011 200 Moretti 2011 208 Yang 2010 191 Mickienė 2011 Results show that when the time-dependent nature of treatment is taken into account appropriately the treatment effects change direction, although none of the results is statistically significant. Adjusting for potential confounders and imputing missing data made little difference to the results.…”
Section: Meta-analysis Of Individual Patient Datamentioning
confidence: 99%
“…Data regarding the use of oseltamivir, an inhibitor of the infl uenza enzyme neuraminidase, 5 have been confl icting with some studies showing shortened duration and severity of seasonal infl uenza infection in adults and children including patients with high-risk conditions. [6][7][8][9][10][11][12][13][14][15][16] However, 2 recent meta-analyses have suggested that although oseltamivir decreases the duration of symptoms or the time to fi rst alleviation of symptoms, it did not decrease the rate of provider-diagnosed pneumonia or hospitalization. 17,18 These new fi ndings arise in part from the fact that 9 randomized controlled trials sponsored by manufacturers had not previously been published in full even though patients agreed to be subjects in a study of what was an experimental medication.…”
Section: Hospital Readmissions Among Children With H1n1 Infl Uenza Inmentioning
confidence: 99%